Orientação para inovação e vantagem competitiva: um estudo na Lar Cooperativa - Mendonça, João Daniel dos Santos (2021)
Innovation has been considered a central theme in organizational studies. This centrality is due to the fact that innovation is connected to the performance of several organizational formats. Although it has been identified as a critical factor in obtaining competitive advantage, few studies have evaluated whether innovation produces statistically significant relationships with competitive advantage in companies. Thus, the objective of this research was to evaluate the relationship between the degree of innovation orientation and competitive advantage at Lar Cooperativa. The study is justified given Lar Cooperativa's vertiginous growth; despite the turbulent environment of pandemics and economic challenges, it manages to remain the sector leader. To this end, the following research problem was formulated: What are the relationships between the degree of innovation orientation and competitive advantage at Lar Cooperativa? To reach the proposed objectives, a quantitative methodology with qualitative fragments was defined, of systematic and empirical observation, making use of a wide documental source, visits and periodic feedbacks to the company. After analyzing the data by means of descriptive statistics and correlation analysis revealed positive associations, although discrete, between innovation and competitive advantage. The results obtained indicated a mature perception of the collaborators regarding the effectiveness of incremental innovation in detriment of radical innovation.